ANALOG TO DIGITAL: THE INDEXICAL FUNCTION OF PHOTOGRAPHIC IMAGES. - Dzenko, Corey (Afterimage)
The article discusses the concept of photographic images as index and the shift from analog to digital image technology. The author believes that digital photography enables greater ease in editing than analog photography because it converts photographs from objects into data. The author argues digital imaging technology disrupts earlier notions of the indexical connection between photographic images and reality.